Ionospheric imaging in Africa. Issue 1 (8th January 2014) - Chartier, Alex T.; Kinrade, Joe; Mitchell, Cathryn N.; Rose, Julian A. R.; Jackson, David R.; Cilliers, Pierre; Habarulema, John‐Bosco; Katamzi, Zama; Mckinnell, Lee‐Anne; Matamba, Tshimangadzo; Opperman, Ben; Ssessanga, Nicholas; et al.
Abstract [1] Accurate ionospheric specification is necessary for improving human activities such as radar detection, navigation, and Earth observation. This is of particular importance in Africa, where strong plasma density gradients exist due to the equatorial ionization anomaly. In this paper the accuracy of three‐dimensional ionospheric images is assessed over a 2 week test period (2–16 December 2012). These images are produced using differential Global Positioning System (GPS) slant total electron content observations and a time‐dependent tomography algorithm. The test period is selected to coincide with a period of increased GPS data availability from the African Geodetic Reference Frame (AFREF) project. A simulation approach that includes the addition of realistic errors is employed in order to provide a ground truth. Results show that the inclusion of observations from the AFREF archive significantly reduces ionospheric specification errors across the African sector, especially in regions that are poorly served by the permanent network of GPS receivers. The permanent network could be improved by adding extra sites and by reducing the number of service outages that affect the existing sites.